Personal Computer Applications Course. - Workman, Robert (ACM, 1984)
A personal computer applications course has been developed. This course is a follow up to an introductory programming course for non-computer science majors. The primary objective of the course is to introduce the major personal computer applications areas: operating system use, word processing, spreadsheet programming, data base management, and communications. For each area, there will be a discussion of its use and related problems. Students will use a representative and a comparison will be made with other systems. The course will be taught using Apple IIe's or Commodore 64 computers. A course outline has been created and approved. The course will be offered for the first time in the Spring of 1984. Budget considerations, the practical difficulties involved with students using copyrighted software, and a desire to have students leave with software they can take with them, make it attractive to use public domain software when possible. Current research is directed towards finding and documenting public domain software for use in this course. Principal sources being investigated are the program libraries of personal computer users groups and educational cooperatives.
Keywords: ABSTRACT ONLY; COMPUTER PROGRAMMING; COMPUTERS, MICROCOMPUTER - Applications; PERSONAL COMPUTER APPLICATIONS COURSE; PUBLIC DOMAIN SOFTWARE; dept.csc